Pillanatképek négy külső-somogyi község lótenyésztéséről a XIX. századi jobbágyfelszabadítást követően - Lanszkiné Széles, Gabriella (Acta Scientiarum Socialium, 2015)
Snapshots of Horse Breeding in Four Villages in Outer Somogy after the 19th Century Serf Emancipation.Fonó, Büssü, Gölle, Kisgyalán villages are located in the valley of River Kapos in Somogy County (Hungary). Horse breeding used to have a considerable role in the valley of Kapos and the villages were recognized as a horse breeder area, which is proved by documents in the Archives of Somogy County, certificates as well as authentic photo collections preserved by farmers. Due to technological, economic and social changes, the circumstances of horse breeding altered significantly during the late 19th and the 20th centuries. The aim of the paper is to analyze this transformation of horse breeding in the four villages. The reminiscences and relics show snapshots from the life of a breeder community such as shows, pedigree registration, or the purchase of horse.
Keywords: Somogy County; horse breeding; purchase of horse; horse name; pedigree registration